Design of a Human Health Monitoring System Based on STM32 - Li, Zihang (International Journal of Mechanical and Electrical Engineering, 2025)
This paper presents a multifunctional health monitoring system based on the STM32F103C8T6 microcontroller, capable of real-time tracking of multiple vital signs, including body temperature, heart rate, blood oxygen saturation, blood pressure, and body posture. Equipped with a Wi-Fi module, the system enables real-time remote monitoring of the user's health status and triggers an alarm upon detection of abnormal health indicators. By integrating multiple sensors in a coordinated manner, the system provides reliable health monitoring and enhances personal safety